Roflumilast - phosphodiesterase inhibitor (PDE4) - new, oral anti-inflammatory drug for treatment of chronic obstructive pulmonary disease - Szmidt, Mirosław (Przewodnik Lekarza/Guide for GPs, 2009)
Looking for new anti-inflammatory drugs in chronic obstructive pulmonary disease (COPD) the attention was paid to inhibitors of phosphodiestrase 4 (PDE4). Its action leads to the increase of cAMP in inflammatory cells and reduces the release of mediators, pro-inflammatory cytokins, free oxygen radicals etc. The most advanced studies are on the selective PDE4 inhibitor - roflumilast (Nycomed). Roflumilast diminishes inflammation in the bronchi; reduces accumulation of eosinophils, neutrophils and macrophages in BALf and lung tissue in study animals and in induced sputum in patients with COPD. The results of large clinical studies published recently show that roflumilast in patients suffering from COPD improved lung function, quality of life and diminished number of exacerbations. Documents for registration of roflumilast have been submitted to the authorities of the European Union and to FDA in USA.